AB0723 Technical aids agreed among specialists for the management of comorbidity in patients with axial spondyloarthritis: the gecoax project. (15th June 2017) - González, C; Curbelo, R; Torre-Alonso, JC; Collantes, E; Castañeda, S; Hernández, MV; Urruticoechea-Arana, A; Nieto, JC; García, J; Abad, MΆ; Ramírez, J; Suárez, C; et al.
Abstract : Background: The management of comorbidity in patients with axial spondyloarthritis (Ax-SpA) needs improvement; the implementation of clinical practice guidelines is still deficient and heterogeneous. Objectives: To prioritise comorbidities in Ax-SpA and to elaborate practical aids for their identification and follow-up. Methods: A multidisciplinary panel [10 rheumatologists (6 experts in Ax-SpA), 2 family doctors, 1 internist, 1 cardiologist, 1 gastroenterologist, 1 psychologist and 3 methodologists] prioritised, in a discussion group, a list of comorbidities based on frequency and impact. Each comorbidity was discussed largely and systematic reviews were performed to support or discard items. In a second meeting, items to be included were presented, discussed, and those with lower priority disregarded. Results: The panel produced a checklist for health professionals and another for patients. Each item is supported by arguments and references. Table 1 shows, schematically, the items included in the checklists. Conclusions: These checklists are intended to facilitate the systematic evaluation of co-morbidity associated with Ax-SpA, thus allowing an earlier detection and better control and management of these patients by the rheumatologist. Acknowledgements: This project was funded by Merck Sharp & Dohme Spain. Merck Sharp & Dohme had no influence on either the development of the project or the final content of the abstract. Disclosure of Interest: None declared